Comparison of Lumbopelvic Movement Patterns in People with and Without Low Back Pain During Stair Descending Task - Neda Namnik; Reza Salehi; Mohammad Jafar Shaterzadeh-Yazdi; Fateme Esfandiarpour; Mohammad Mehravar; Neda Orakifar (Shiraz University of Medical Sciences, 2018)
Background: Decreased lumbar spine control may be associated with early and/ or excessive lumbopelvic motion with trunk and lower extremity movements during functional and daily activities. This study investigated differences in lumbopelvic movement patterns in people with and without low back pain (LBP) during a stair descending (SD) task. Methods: A total of 36 subjects, 18 females with non-specific chronic low back pain (NSCLBP) and 18 healthy females, participated in this study. A threedimensional motion capture system was used to record kinematics during the SD task. Results: The results showed that in the LBP group, the start-time of the lumbar muscles occurred early in the movement (P=0.015). Additionally, subjects with LBP showed excessive lumbar spine and pelvic movement during the SD task (P<0.05). Conclusion: LBP patients make early and excessive lumbopelvic movements during a SD task, and this can be an important factor contributing to the development or persistence of their LBP problem. This finding should be considered by clinicians when evaluating functional tasks as part of movementbased examinations and rehabilitation programs for people with LBP